Thats something interesting! (part 2)

a ! b ! = a ! + b ! + 2 c a! b! = a! + b! + 2^c

Given that a , b , c a,b,c are positive integers satisfying the above equation. What is the value of a + b + c a+b+c ?

Also try part1


The answer is 7.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Nihar Mahajan
Feb 19, 2015

Without loss of generality let us assume that a b \large a \geq b and divide through by b ! \large b! :

a ! = a ! b ! + 1 + 2 c b ! \large a! = \dfrac{a!}{b!} + 1 +\dfrac{2^c}{b!} , giving integers throughout.

As each term on the RHS is integer, R H S 3 a ! 3 a 3 \large RHS \geq 3 \Rightarrow a!\geq 3 \Rightarrow a\geq 3

For b > 2 \large b > 2 , b ! \large b! will contain a factor of 3 \large 3 , and so cannot divide 2 c \large 2^c .

Thus b = 1 , o r , b = 2 \large b=1 ,or, b=2

If b = 1 a ! = a ! + 1 + 2 c \large b=1\Rightarrow a! = a! + 1 + 2^c , which leads to 2 c + 1 = 0 : \large 2^c + 1 = 0: no solution.

If b = 2 , a ! = a ! 2 + 1 + 2 c 1 \large b=2,\Rightarrow a! = \dfrac{a!}{2} + 1 + 2^{c - 1} , which leads to a ! 2 = 1 + 2 c 1 \large \dfrac{a!}{2} = 1 + 2^{c -1}

If a > 3 a ! 2 \large a > 3 \Rightarrow \dfrac{a!}{2} is even, so 2 c 1 = 1 \large 2^{c - 1} = 1 . But then we get a ! 2 = 2 \large \dfrac{a!}{2} = 2 no solution.

If a = 3 , 3 = 1 + 2 c 1 c = 2 \large a = 3, 3 = 1 + 2^{c - 1} \Rightarrow c = 2

Hence we obtain the only solution: 3 ! 2 ! = 3 ! + 2 ! + 2 2 \large 3!2! = 3! + 2! + 2^2

Thus, a + b + c = 3 + 2 + 2 = 7 \large a + b + c = 3 + 2 + 2 =\huge \boxed{7} .

Curtis Clement
Feb 19, 2015

Assume without loss of generality that a b \large a \geq b . Now dividing by b ! \large b! gives a ! = a ! b ! + 1 + 2 c b ! a! = \frac{a!}{b!} + 1 + \frac{2^c}{b!} This means that b = 1 o r 2 \large b = 1 \ or \ 2 . For b = 1 \large b =1 we get 1 + 2 c = 0 \large 1+2^c = 0 so b = 2 \large b = 2 \Rightarrow a ! = a ! 2 + 1 + 2 c 1 2 c 1 + 1 = a ! 2 \large a! = \frac{a!}{2} + 1 + 2^{c-1} \Rightarrow\ 2^{c-1} + 1= \frac{a!}{2} . This means that a ! 2 \large \frac{a!}{2} must be odd so the exponent of 2 in the factorial is 1. Hence, (as 2 c 1 2^{c-1} > 0 ) a = 3 \large a = 3 and c = 2 \large c = 2

\therefore a + b + c = 3 + 2 + 2 = 7 \large a+b+c = 3+2+2 = \boxed{7}

Tanish Singhal
Feb 20, 2015

Done through hit and trial method...

Incredible Mind
Feb 22, 2015

just guess

Vaibhav Prasad
Feb 19, 2015

2 ! × 3 ! = 2 ! + 3 ! × 2 2 2!\times 3!=2!+3!\times { 2 }^{ 2 }

Hence 2 + 3 + 2 = 7 2+3+2=7

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...